Desain Aplikasi Pengindeksan Dasar-Dasar Hukum Al Quran Berbasis Web - Herwanto, Ferry; , Hernawan Sulistyanto, S.T., M.T (2017)
Quran is one of the foundations of Islamic law in addition to Hadiths, but there are a lot of Muslims whom don't understand the Quran. The function of the Quran is as a guide, a warning, lesson for mankind especially Muslims and as a miracle of prophet Muhammad. The content of the Qur'an is very broad, the Quran contains information about ethics, universe, medical, legal and life sciences. Because the content of the Quran is very broad hence made the Quran indexing applications to facilitate the general public, especially the Muslims to understand their holy book itself, namely the Quran. Thought the point of this study is how to design applications that provide Quran indexes search feature that the results are topics, subtopics, surah, and verses and each verse's audio can be heard. Topics are the general theme and subtopics are parts or branches of the topic concerned. the purpose of this study was to design an application that indexing the Quran and easy to use web-based and can be accessed anywhere and anytime. Application developed using waterfall model and using MYSQL, PHP as server side scripting, HTML, CSS, JavaScript as client side scripting. The application can provide faster result in searching index Al quran and help the user understand Al quran based-on the questionnaire test with 3 ustadz as respondent get 87.55% and 24 general users get 89.8%.